Peningkatan Kepercayaan Diri Siswa Kelas X SMK yang Mengalami Kecemasan Berbicara di Depan Kelas Melalui Layanan Bimbingan Kelompok Teknik Role Playing - Juniati Juniati; Erwin Ambalinggi; Asyumi Febrianti (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The development of a student's personality, particularly during classroom interaction, is heavily influenced by their level of self-confidence. A lack of self-assurance often leads to public speaking anxiety, which subsequently restricts student engagement and diminishes academic performance. This phenomenon is frequently identified among tenth-grade Vocational High School (SMK) students who are navigating a period of environmental transition. This research focuses on enhancing the self-confidence of Grade X SMK students struggling with speech-related anxiety through the implementation of group guidance services utilizing role-playing methods. The study follows a Guidance and Counseling Action Research (GCAR) design conducted over two cycles, consisting of preparatory, executive, monitoring, and evaluative phases. The participants were tenth-grade students with low self-confidence profiles as determined by questionnaires and field observations. Data were analyzed using a descriptive quantitative approach to compare performance levels before and after the intervention. The results demonstrate that group guidance integrated with role-playing is an effective strategy for optimizing student self-confidence, as shown by the consistent upward trend in scores throughout the cycles. These findings suggest that this technique serves as a strategic instrument for school counselors to mitigate social anxiety among students.